The potential of Zai pit technology and Integrated soil fertility management to enhance crop productivity in semi-arid regions of Sub-Sahara Africa: A review - Kebenei, Mercy Cheruto; Mucheru-Muna, Monicah; Muriu-Ng’ang’a, Felista (International Journal of Environment, Agriculture and Biotechnology, 2023)
Low and continuously deteriorating soil fertility coupled with frequent droughts and extended mid-season dry spells scenarios brought about by low and unreliable rainfalls have had a significant negative influence on agricultural productivity in most semi-arid regions of the world. The farmers' limited capacity to change their farming practices and adjust to the changing climatic circumstances further exacerbates these effects. Various in-field rainwater collection techniques, including Zai pits, have been promoted in recent years to assist farmers, particularly in dry and semi-arid locations, to harvest, store, and use rainfall for increased crop productivity. Zai pit is a form of dryland farming technique that involves the unitization of holes or troughs aimed at ensuring soil maintenance, soil erosion control and water preservation in agricultural fields. Additionally, combining effective soil fertility management strategies, such as integrated soil fertility management, with rainwater harvesting methods has the potential to further boost crop yields. Integrated soil fertility management involves the combined use of inorganic fertilizers and organic fertilizers such as cattle manure with the aim of improving soil fertility. Zai pit technology and integrated soil fertility management techniques have been utilized as climate smart agricultural approaches to reduce soil moisture stress and improve crop productivity in arid and semi-arid regions. This paper reviews previous research results on crop productivity as influenced by Zai pit technology and integrated soil fertility management techniques.